Clinical features of Japanese polycythemia vera and essential thrombocythemia patients harboring CALR, JAK2V617F, JAK2Ex12del, and MPLW515L/K mutations. (January 2016) - Okabe, Masahiro; Yamaguchi, Hiroki; Usuki, Kensuke; Kobayashi, Yutaka; Kawata, Eri; Kuroda, Junya; Kimura, Shinya; Tajika, Kenji; Gomi, Seiji; Arima, Nobuyoshi; Mori, Sinichiro; Ito, Shigeki; et al.
Highlights: We assessed the clinical features and genetic mutations of Japanese MPN patients. The clinical features of JAK2V617F and CALR mutation ET differ. We did not find a correlation between CALR mutations and the 46/1 haplotype. CALR mutation ET had a lower incidence of thrombosis relative to JAK2V617F ET. Abstract: The risk of complication of polycythemia vera (PV) and essential thrombocythemia (ET) by thrombosis in Japanese patients is clearly lower than in western populations, suggesting that genetic background such as race may influence the clinical features. This study aimed to clarify the relationship between genetic mutations and haplotypes and clinical features in Japanese patients with PV and ET. Clinical features were assessed prospectively among 74 PV and 303 ET patients. There were no clinical differences, including JAK2V617F allele burden, between PV patients harboring the various genetic mutations. However, CALR mutation-positive ET patients had a significantly lower WBC count, Hb value, Ht value, and neutrophil alkaline phosphatase score (NAP), and significantly more platelets, relative to JAK2V617F -positive ET patients and ET patients with no mutations. Compared to normal controls, the frequency of the JAK2 46/1 haplotype was significantly higher among patients with JAK2V617F, JAK2Ex12del, or MPL mutations, whereas no significant difference was found among CALR mutation-positive patients. CALR mutation-positive patients had a lower incidence of thrombosis relative to JAK2V617F- positive patients. Our findings suggest that JAK2V617F -positive ET patients and CALR mutation-positive patients have different mechanisms of occurrence and clinical features of ET, suggesting the potential need for therapy stratification in the future.